Insights into photovoltaic properties of ternary organic solar cells from phase diagrams. Issue 1 (31st December 2018) - Makha, Mohammed; Schwaller, Philippe; Strassel, Karen; Anantharaman, Surendra B.; Nüesch, Frank; Hany, Roland; Heier, Jakob
ABSTRACT: The efficiency of ternary organic solar cells relies on the spontaneous establishment of a nanostructured network of donor and acceptor phases during film formation. A fundamental understanding of phase composition and arrangement and correlations to photovoltaic device parameters is of utmost relevance for both science and technology. We demonstrate a general approach to understanding solar cell behavior from simple thermodynamic principles. For two ternary blend systems we construct and model phase diagrams. Details of EQE and solar cell parameters can be understood from the phase behavior. Our blend system is composed of PC70 BM, PBDTTT-C and a near-infrared absorbing cyanine dye. Cyanine dyes are accompanied by counterions, which, in a first approximation, do not change the photophysical properties of the dye, but strongly influence the morphology of the ternary blend. We argue that counterion dissociation is responsible for different mixing behavior. For the dye with a hexafluorophosphate counterion a hierarchical morphology develops, the dye phase separates on a large scale from PC70 BM and cannot contribute to photocurrent. Differently, a cyanine dye with a TRISPHAT counterion shows partial miscibility with PC70 BM. A large two-phase region dictated by the PC70 BM: PBDTTT-C mixture is present and the dye greatly contributes to the short-circuit current. Graphical Abstract: